Studies On Mass Transfer Characteristics Of Palm Kernel Oil Extraction Using Supercritical Carbon Dioxide - Ismail, Norhuda (2005)
To exploit further the application of supercritical carbon dioxide (SC-COz) extraction, as a simplified and environmental friendly process, a study on the palm kernel oil yield, fundamental of diffusivity and mass transfer coefficients of palm kernel oil in situation of overall single palm kernel and a packed-bed column of the overall single palm kernels was studied. The study also incorporated mathematical models formulation for describing the mass transfer phenomena of palm kernel oil at the supercritical conditions. Thus, this study has focused on the candidate sample of overall single palm kernels of size 6 mm (outside diameter) by using a laboratory Supercritical Carbon Dioxide (SC-CO2) equipment. The experimental runs of the supercritical conditions considered in this study vary in a range of temperatures and pressures of 40 °C, 50 °C, 60 °C, 70 °C and 80 °C and pressures of 27.6 MPa, 34.5 MPa, 41.4 MPa and 48.3 MPa respectively for an overall single palm kernel, and at a constant temperature of 50 °C, 60 °C and 70 °C and within the same pressure range for a packed bed of overall single palm kernels. The findings of this study on an overall single palm kernel, demonstrated that first, the laboratory SC-CO2 extraction process managed to extract a maximum yield of 5 percent PKO at the best supercritical conditions of temperature 80 °C and pressure 48.3 MPa respectively. Secondly, the solubility of PKO in SC-CO2 increases with temperatures at a particular constant pressure, and likewise increases with pressures at a particular constant temperature. Thirdly, the study shows that the diffusion coefficients of PKO at the supercritical condition, based on an overall single palm kernel, is strongly dependent on pressures from 27.6 MPa to 48.3 MPa, at each constant temperature of 50 °C, and 60 °C.